Chemistry :An Introduction to General,Organic,& Biological Chemistry - Timberlake, Karen C. ([S.l.] : Benjamin Cummings, 2000)
This best-seller, now in a Media Update, makes chemistry exciting to readers by showing why important concepts are relevant to their lives and future careers. The writing is exceptionally friendly. Sample problems teach readers how to solve chemical problems, and thousands of practice problems help readers develop problem-solving techniques and critical thinking skills. This edition contains more conceptual problems than ever before and has also been redesigned to accommodate new styles of learning and teaching. The Media Update includes The Chemistry Place Special Edition for Timberlake (www.chemplace.com/college), a text-specific web site and two new CD-ROMs: The Chemistry of Life CD-ROM for Introductory Chemistry and the Chemistry Study Pack CD-ROM 2.0. The book is suitable for courses that precede general chemistry and for those with no previous background in chemistry who are preparing for health-related careers in nursing, respiratory therapy, dental technology, dietetics, nuclear technology, agriculture, or teacher education. For college instructors and students.
Keywords: chemistry,organic,biological chemistry